The Effectiveness of Gemini AI-Generated Imagery towards Junior High School Students Writing Skills - Wahyu Hendrawan; Zainul Aminin (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the effect of Gemini AI-generated imagery on junior high school students’ descriptive writing skills. Gemini-generated visuals are hypothesized to help students generate ideas, enrich vocabulary, and develop more detailed descriptions by providing concrete visual prompts. The researchers employed a pre-experimental method using one-group pretest–posttest design to determine the effect of Gemini AI-generated imagery on students’ descriptive writing performance. The study involved 30 seventh-grade students and was conducted over five meetings, consisting of one pre-test session, three treatment sessions, and one post-test session. Before the treatment, the students’ mean pretest score was 60.58. After the treatment, the mean posttest score increased to 67.78, resulting a mean gain of 7.20 points. A paired-samples t-test indicated a statistically significant improvement (p .001), with a large effect size (d = 1.34). The study concludes that integrating Gemini AI-generated imagery into writing instruction can effectively improve students’ descriptive writing skills.